Penerapan Strategi Pembelajaran Crossword Puzzle untuk Meningkatkan Hasil Belajar IPS Siswa Sekolah Dasar Negeri - Masripah Masripah; Nurul Fatonah; Yufi Mohammad Nasrullah; Nurhasanah Nurhasanah (Allimna: Jurnal Pendidikan Profesi Guru, 2023)
The teacher's role in managing learning is very important. The teacher must have a relevant strategy so that students can achieve learning outcomes according to predetermined criteria. However, in practice, many student learning outcomes in social studies subjects in class V at SDN Girimukti I Cikelet do not meet the KKM. So to solve these problems, a solution is given through a more relevant learning strategy, namely the Crossword Puzzle learning strategy. This study uses a quantitative approach. This research was conducted by raising the problem of how to apply the Crossword Puzzle Learning Strategy to improve student learning outcomes in Social Science subjects for class V SDN Girimukti I Cikelet, Garut Regency. This study aimed to determine the application of the Crossword Puzzle Learning Strategy to improve social studies learning outcomes for fifth-grade students at SDN Girimukti I Cikelet, Garut Regency.